Loss of the Essential Autophagy Regulators FIP200 or Atg5 Leads to Distinct Effects on Focal Adhesion Composition and Organization - Assar, Emelia A.; Tumbarello, David A. (Frontiers in Cell and Developmental Biology, 2020)
Autophagy is an essential catabolic intracellular pathway that maintains homeostasis by degrading long-lived proteins, damaged organelles, and provides an energy source during nutrient starvation. It is now understood that autophagy has discrete functions as a selective lysosomal degradation pathway targeting large cytosolic structural and signalling complexes to influence cell motility and adhesion. We provide evidence suggesting the primary autophagy regulators Atg5 and FIP200 both play a role in cell motility and extracellular matrix adhesion. However, their loss of function has a differential impact on focal adhesion composition and organisation, as well as signalling in response to fibronectin induced cell spreading. This differential impact on focal adhesions is illustrated by smaller focal adhesion complexes and a decrease in FAK, paxillin, and vinculin expression associated with FIP200 loss of function. In contrast, Atg5 loss of function results in production of large and stable focal adhesions, characterised by their retention of phosphorylated FAK and Src, which correlates with increased vinculin and FAK protein expression. Importantly, autophagy is upregulated during processes associated with focal adhesion reorganisation and their exhibits colocalisation of autophagosomes with focal adhesion cargo. Interestingly, FIP200 localises to vinculin-rich focal adhesions and its loss negatively regulates FAK phosphorylation. These data collectively suggest FIP200 and Atg5 may have both autophagy-dependent and -independent functions that provide distinct mechanisms and impacts on focal adhesion dynamics associated with cell motility.